2015
DOI: 10.1016/j.eururo.2014.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanisms of Androgen Deprivation Resistance in Prostate Cancer at the Molecular Level

Abstract: Context To evaluate molecular mechanisms that play a role in the development of resistance to androgen deprivation therapy in castration-resistant prostate cancer. Objective The understanding of mechanisms and biological pathways associated with the progression of prostate cancer under systemic androgen depletion or administration of novel anti-androgens abiraterone, enzalutamide and ARN-509. This review also examines the introduction of novel combinational approaches for patients with castrate resistant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
196
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(212 citation statements)
references
References 90 publications
2
196
2
5
Order By: Relevance
“…Previous human studies identified that patients with metastatic PCa with low serum testosterone levels had a worse response to endocrine therapy compared with patients with high serum testosterone levels (33,38). Notably, data from the present study is consistent with the general model of oncogene derepression as a mechanism of PCa progression (40). In this model, inhibition of AR function can lead to derepression of oncogenes that are normally repressed by the fully functional AR, leading to PCa progression.…”
Section: Testosterone Levels ----------------------------------------supporting
confidence: 80%
“…Previous human studies identified that patients with metastatic PCa with low serum testosterone levels had a worse response to endocrine therapy compared with patients with high serum testosterone levels (33,38). Notably, data from the present study is consistent with the general model of oncogene derepression as a mechanism of PCa progression (40). In this model, inhibition of AR function can lead to derepression of oncogenes that are normally repressed by the fully functional AR, leading to PCa progression.…”
Section: Testosterone Levels ----------------------------------------supporting
confidence: 80%
“…PCa is initially managed with surgery, radiation, androgen antagonists (e.g., bicalutamide), and surgical or chemical castration. However, relapsed or metastatic disease after castration [castration-recurrent prostate cancer (CRPC)] has a poor prognosis, with most patients dying within 2 years (Karantanos et al, 2015). Innovative approaches are urgently needed to treat patients with CRPC.…”
Section: Introductionmentioning
confidence: 99%
“…При этом существуют подтвержденные данные, что около 60% больных с биохимическими рецидивами, резистентных к андрогенной депривации, отвечают на вторую линию гормональной терапии. Это отмечено при применении разных групп препаратов, блокирующих активацию ан-дрогенной оси [6][7][8]11]. Представлены результаты лечения 112 больных метастатическим кастратрезистентным раком предстательной железы (мкррПж) с использованием ингибитора биосинтеза андрогенов абиратерона ацетата во второй линии гормональной терапии.…”
unclassified
“…При этом существуют подтвержденные данные, что около 60% больных с биохимическими рецидивами, резистентных к андрогенной депривации, отвечают на вторую линию гормональной терапии. Это отмечено при применении разных групп препаратов, блокирующих активацию ан-дрогенной оси [6][7][8]11]. Критичным ферментом в синтезе андрогенов являет-ся цитохром (CYP17A).…”
unclassified